2021
DOI: 10.1055/s-0041-1735919
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19–Associated Bone Marrow Necrosis—A Case Report

Abstract: We report, herein, a rare case of vertebral bone marrow necrosis in a patient at 1-month post–novel coronavirus disease 2019 (COVID-19) pneumonia complicated with disseminated intravascular coagulation (DIC). The commonly observed radiological features on the imaging modalities like computed tomography (CT), magnetic resonance imaging (MRI), and 18-F fluorodeoxyglucose positron emission tomography (FDG PET) have been discussed here followed by a brief discussion on the role of in-phase and opposed-phase imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Four studies [ 50 , 51 , 53 , 54 ], overall involving 228 patients, focused on AVN of the hip, and two studies (5 patients) [ 47 , 48 ] focused exclusively on the knee. The other studies included patients with AVN deriving from mixed areas of the body (spine, pelvis, shoulder) [ 49 , 52 , 55 ]. Study generalities and data of the patients are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Four studies [ 50 , 51 , 53 , 54 ], overall involving 228 patients, focused on AVN of the hip, and two studies (5 patients) [ 47 , 48 ] focused exclusively on the knee. The other studies included patients with AVN deriving from mixed areas of the body (spine, pelvis, shoulder) [ 49 , 52 , 55 ]. Study generalities and data of the patients are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…A coagulopathy has been reported in up to 50% of patients with severe COVID-19 manifestations [ 4 ]. Infection-induced endothelial dysfunction causes an excess of procoagulant thrombin with concomitant shutting down of the fibrinolytic cascade resulting in a hypercoagulable state which can spur thrombosis by increasing blood viscosity and coupled with hypoxia can activate the hypoxia-induced transcription factor-dependent signalling [ 5 ]. SARS-CoV-2 ORF3a protein and host hypoxia-inducible factor (HIF-1Þ) play key role in the virus infection and pro-inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover the virus binds to the angiotensin-converting enzyme 2 (ACE-2) receptors and leads to activation and redistribution of immune cells [32][33][34][35]. There have been many references in the literature regarding the development of autoimmune diseases including granulomatous diseases as well as bone marrow involvement in patients following COVID-19 [36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%